Konstruksi Sosial Masyarakat terhadap Dukun Suwuk di Desa Tanjung Lor, Kabupaten Pacitan - Putri, Nesti Eka; Apriadi, Deny Wahyu (Sociology Department Of Syiah Kuala University, 2023)
Although advanced modern healthcare facilities are available today, alternative healing practices such as Suwuk traditional healers still persist. The purpose of this article is to explain the social construction that occurs in society regarding Suwuk phenomenon, which is performed by traditional healers as an alternative treatment technique. A qualitative approach with a case study design is employed in this article. The study indicates that individuals' decisions to choose Suwuk healing are influenced by internal and external factors. Internal factors include patients' beliefs, trust in Suwuk healing, and their desire for recovery. External factors encompass economic aspects such as treatment fees and patients' income, distance to Suwuk healers compared to medical healthcare facilities, as well as the influence and advice from others as a form of intergenerational belief. The construction of Suwuk healers is shaped by patients' experiences and successes in undergoing treatments with Suwuk healers, which then form subjective awareness of the subject. Environmental factors, including the cultural environment and intergenerational beliefs, influence the objective awareness of society towards Suwuk healing services. Objective awareness of the community is formed through three phases: externalization as an adaptation to the long-standing belief in the existence of Suwuk healers, objectification as a search for information about such healing practices, and acceptance or internalization of alternative Suwuk healing in daily life.AbstrakMeskipun fasilitas kesehatan modern yang maju saat ini tersedia, praktik pengobatan alternatif seperti dukun Suwuk tetap ada. Tujuan artikel ini adalah menjelaskan konstruksi yang terjadi pada masyarakat terkait pengobatan Suwuk yang dilakukan oleh praktisi dukun sebagai teknik pengobatan alternatif. Pendekatan kualitatif dengan desain studi kasus digunakan dalam artikel ini. Kajian ini menunjukkan bahwa keputusan individu dalam memilih pengobatan dukun Suwuk dipengaruhi oleh faktor internal dan faktor eksternal. Faktor internal meliputi keyakinan dan kepercayaan pasien terhadap pengobatan Suwuk serta keinginan untuk sembuh. Faktor eksternal mencakup faktor ekonomi seperti tarif pengobatan dan pendapatan pasien, jarak tempuh ke dukun Suwuk dibandingkan dengan fasilitas kesehatan medis, serta pengaruh dan saran dari orang lain sebagai bentuk kepercayaan turun-temurun antargenerasi. Konstruksi terhadap dukun Suwuk dibentuk melalui pengalaman dan keberhasilan pasien dalam menjalani pengobatan dengan dukun Suwuk, yang kemudian membentuk kesadaran subjektif terhadap objek tersebut. Faktor lingkungan tinggal, termasuk lingkungan budaya dan kepercayaan antar generasi, mempengaruhi kesadaran objektif masyarakat terhadap jasa pengobatan dukun Suwuk. Kesadaran objektif masyarakat terbentuk melalui tiga fase, yaitu fase eksternalisasi sebagai adaptasi terhadap keberadaan dukun Suwuk yang telah dipercayai sejak lama, fase obyektivikasi sebagai pencarian informasi tentang pengobatan tersebut, dan fase penerimaan atau internalisasi pengobatan alternatif dukun Suwuk dalam kehidupan sehari-hari.